Soil Metals and Ectomycorrhizal Fungi Associated with American Chestnut Hybrids as Reclamation Trees on Formerly Coal Mined Land - J. M. Bauman; J. Adamson; R. Brisbin; E. T. Cline; C. H. Keiffer (International Journal of Agronomy)
Hybrid chestnut (Castanea dentata × C. mollissima) has the potential to provide a valuable agroforestry crop on formerly coal mined landscapes. However, the soil interactions of mycorrhizal fungi and buried metals associated with mining are not known. This study examined soil, plant tissue, and ectomycorrhizal (ECM) root colonization on eight-year-old hybrid (BC1F3 and BC2F3) and American chestnuts on a reclaimed coal mine in Ohio, USA. Chestnut trees were measured and ECM colonization on roots was quantified. Leaves, flowers, and soil were analyzed for heavy metals. Differences were not detected among tree types regarding metal accumulation in plant tissue or ECM colonization. BC2F3 hybrids had greater survival and less cankers than American chestnuts (P = 0.006 and <0.0001). Taller trees were associated with greater ECM root colonization and correlated with an increase in Al uptake (P = 0.02 and 0.01). When comparing tissue, manganese and aluminum were in higher concentrations in leaves than flowers, where copper and selenium were significantly higher in floral tissue (P < 0.05). All trees were flowering at this time meriting further examination in nut tissue. Block effects for selenium and zinc indicate the variability in reclaimed soils requiring further monitoring for possible elemental transfer to nut and wood tissue.